Swiss Army Pathogen: The Salmonella Entry Toolkit - Hume, Peter J.; Singh, Vikash; Davidson, Anthony C.; Koronakis, Vassilis (Frontiers in Cellular and Infection Microbiology, 2017)
Salmonella causes disease in humans and animals ranging from mild self-limiting gastroenteritis to potentially life-threatening typhoid fever. Salmonellosis remains a considerable cause of morbidity and mortality globally, and hence imposes a huge socio-economic burden worldwide. A key property of all pathogenic Salmonella strains is the ability to invade non-phagocytic host cells. The major determinant of this invasiveness is a Type 3 Secretion System (T3SS), a molecular syringe that injects virulence effector proteins directly into target host cells. These effectors cooperatively manipulate multiple host cell signalling pathways to drive pathogen internalisation. Salmonella does not only rely on these injected effectors, but also uses several other T3SS-independent mechanisms to gain entry into host cells. This review summarises our current understanding of the methods used by Salmonella for cell invasion, with a focus on the host signalling networks that must be coordinately exploited for the pathogen to achieve its goal.